#### Answer

(x+12y)(x+2y)

#### Work Step by Step

$x^{2}$+14xy +24$y^{2}$=$x^{2}$+2xy+12xy +24$y^{2}$=
x(x+2y)+12y(x+2y)=
(x+12y)(x+2y)

Published by
Pearson

ISBN 10:
0321726391

ISBN 13:
978-0-32172-639-1

(x+12y)(x+2y)

$x^{2}$+14xy +24$y^{2}$=$x^{2}$+2xy+12xy +24$y^{2}$=
x(x+2y)+12y(x+2y)=
(x+12y)(x+2y)

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.